2016
DOI: 10.1287/mnsc.2015.2321
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Losing in a Competition on the Willingness to Seek Further Challenges

Abstract: How do people react to setbacks and successes? I use a laboratory experiment to determine the effect of winning and losing in a competition on the willingness to seek further challenges. Participants compete in two-person tournaments in an arithmetic task and are then informed of their score and the outcome of the competition. Participants then have to decide on a performance target for a second round: the higher the target, the higher the potential reward, but participants who do not reach the target earn not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 47 publications
3
55
1
Order By: Relevance
“…19 For those who initially pick the piece rate, the gender difference in the reaction to positive feedback drops by 36 percent. Past studies have shown that women might perform worse after losing in a competition compared to men in the same situation (Buser, 2016;Gill and Prowse, 2014). In column 4, we control for normalised rank (that is, likelihood of winning) in each round.…”
Section: Beliefs and Performancementioning
confidence: 99%
“…19 For those who initially pick the piece rate, the gender difference in the reaction to positive feedback drops by 36 percent. Past studies have shown that women might perform worse after losing in a competition compared to men in the same situation (Buser, 2016;Gill and Prowse, 2014). In column 4, we control for normalised rank (that is, likelihood of winning) in each round.…”
Section: Beliefs and Performancementioning
confidence: 99%
“…Losses determine a reduction in effort for women, while for men productivity is affected only when the prize at stake is large enough. Buser (2014) implements an experiment in which participants compete in a two-person tournament and after having been informed on the outcome of the competition have to decide on a performance target for a second round. He finds that while men losing the first round go for a more challenging target but perform worse in the second 5 round, women do not change their target, but lower their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, succeeding at sports is often credited for building self-esteem in children which helps them perform well in other spheres, such as at school or when interacting with their peers. While the previous literature has investigated extensively the impact of relative feeback on belief updating and on goal setting and competitiveness within the same task (e.g., Eriksson et al 2009;Azmat and Iriberri 2010;Gill and Prowse 2012;Wozniak et al 2015;Buser 2016), it is almost silent on the across-task impact of feedback.…”
Section: Introductionmentioning
confidence: 99%